إسهامات الباحثين الجزائريين في دراسة الأدب الجزائري القديم، عصر دولة بني حمَّاد أنموذجا - غازي, سيدي علي (جامعة الوادي - university of Eloued, 2021)
يروم هذا البحث كشف جهود الجزائريين في دراسة الأدب الجزائري القديم من خلال تسليط الضوء على عصر دولة بني حمّاد في الشعر والنثر، وهذا بالوقوف عند دراسات أسهمت في إحياء الأدب الجزائري القديم، وبعثه في المكتبات الوطنية والعربية، انطلاقا من جهود مختار حبار في تدوين سير و تراجم الشعراء، ثم أحمد أبو رزاق في طرقه لموضوع الأدب الحمادي، ومحمد الطمار من خلال تأريخه للخطاب الشعري الجزائري، وصولا عند مساهمة محمد مرتاض في دراسة الشعر الوجداني وفق المنهج التكاملي. This research reveals the efforts of the Algerians in the study of the Ancient Algerian literature through highlighting the Hammadid Era in prose and poetry, this is by stopping at some studies that have contributed to the revival of the Ancient Algerian literature, and spreading it in national and arab libraries, starting from the efforts of Mokhter Habbar in writing poets’ biographies and autobiographies, Ahmed Abu Razak’s tackling of Hamadid literature,and through the presence of the Algerian poetic discourse in Muhammad Al-Tammar’s historical texts, to Muhammad Murtadh’s contribution in studying emotional poetry through integrative approach.
مقال
Keywords: الأدب الجزائري القديم ; دولة بني حمَّاد ; سير و تراجم ; الأدب الحمَّادي ; الخطاب الشعري الجزائري